CINEMAS, THEATERS, AND MUSEUMS IN UZBEKISTAN ECONOMIC DEVELOPMENT. DEVELOPMENT STRATEGIES OF THE REPUBLIC OF UZBEKISTAN - Teshaboyeva Nafisa Zubaydulla qizi; Isoqova Muxlisa Sherzod qizi (TADQIQOTLAR.UZ, 2024)
Annotation: Uzbekistan's cultural scene is enriched by a variety of cinemas, theaters, and museums that contribute to the country's vibrant artistic landscape. Cinemas like the Alisher Navoi Cinema Palace and Cinema Park entertain audiences with a selection of local and international films, reflecting a blend of traditional storytelling and modern cinematic trends. Theaters such as the Alisher Navoi Theatre and Ilkhom Theatre offer a stage for diverse performances, from classic operas and ballets to contemporary and experimental plays, nurturing the performing arts. Museums across the nation, including the State Museum of History of Uzbekistan and the Amir Timur Museum, preserve and exhibit the rich tapestry of Uzbek heritage, displaying artifacts that span centuries of history. These institutions play a pivotal role in the cultural life of Uzbekistan, preserving its past, showcasing its artistic endeavors, and educating future generations.